PERTANGGUNGJAWABAN NAKHODA PADA PERISTIWA KECELAKAAN KAPAL MENURUT UNDANG-UNDANG PELAYARAN - Hasrianto Hasrianto (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractThe master is the ship’s leader who is responsible for all the events that occur on the ship. The master is also responsible for when an accident occurs, even if it does not cause death. If the skipper causes the accident, the skipper can be held responsible and subject to administrative sanctions. The legal liability of the skipper in the event of a ship accident according to Law Number 17 of 2008 is regulated in Article 249, where a ship accident which is an event experienced by a ship can threaten the safety of the ship and/or human life in the form sinking ships, burning ships, collision ships, and aground vessels are the responsibility of the master unless it can be proven otherwise. The legal consequences of the skipper in the event of a ship accident according to the Shipping Act as referred to in Article 253 of Law Number 17 of 2008, in the form of administrative sanctions in the form of a warning or temporary revocation of Seaman Skill Certificate. Keywords : Helmsman, Legal Liability, Ship Accident